3D Printing of Shiitake Mushroom Incorporated with Gums as Dysphagia Diet - Liu, Zhenbin; Bhandari, Bhesh; Guo, Chaofan; Zheng, Wenqi; Cao, Shangqiao; Lu, Hongyu; Mo, Haizhen; Li, Hongbo (Foods, 2021)
With the speeding tendency of aging society, the population experienced dysphagia is increasing quickly. Desirable dysphagic diets should be safe, visually appealing and nutritious. 3D printing allows for creation of personalized nutritious foods with regular-like appearance. Shiitake mushroom, rich in protein and bioactive compounds, is suitable for elderly, but its hard texture was not friendly to the elderly with dysphagia. This study investigated the feasibility of production of dysphagic product using shiitake mushroom by 3D printing with various gums addition, including arabic gum (AG), xanthan gum (XG) and k-carrageenan gum (KG) at concentrations of 0.3%, 0.6% and 0.9% (w/w). Data suggested that XG and KG incorporation significantly increased inks’ mechanical strength by decreasing water mobility and promoting the formation of hydrogen bond, enabling 3D printed objects with great self-supporting capacity. The XG containing and KG-0.3% samples were categorized into level 5—minced and moist dysphagia diet within international dysphagia diet standardization initiative (IDDSI) framework. AG addition decreased mechanical strength and viscosity, hardness and self-supporting capacity of 3D printed constructions. AG-0.3% and AG-0.6% samples could not be classified as dysphagia diets based on IDDSI tests. This study provides useful information for dysphagia diet development with appealing appearance by 3D printing.